THE EFFECT OF ORGANIZATIONAL SUPPORT AND ORGANIZATIONAL COMMITMENT TO EMPLOYE PEFORMANCE (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2018)
This study aims to determine the direct effect between (1) organizational support with job performance, (2) organizational commitments with job performance, (3) organizational support with organizational commitment. The method used is a survey method with a correlation approach. In this study serve as a sample of 81 employees were selected based on random techniques (simple random samplinng). Data were obtained by spreading questioner. This study was conducted in Dinas Kesehatan Kota Metro. Based on hypothesis testing that has been done, it can be described as the following research findings: (1) there is a positive direct influence of organizational support with job performance, (2) there is a positive direct influence of organizational commitmen on job performance, (3) there is a positive direct influence between organizational support on organizational commitment. The implication of this research is an attempt to improve employee’s job performance can be done by improving organizational support and commitment.